Supportive self-management program for people with chronic headaches and migraine: a randomized controlled trial and economic evaluation - Underwood, M; Achana, F; Carnes, D; Eldridge, S; Ellard, D; Griffiths, F; Haywood, K; Hee, SW; Higgins, H; Mistry, D; Mistry, H; Newton, S; et al. (American Academy of Neurology, 2022)
Background and Objectives Chronic headache disorders are a major cause of pain and disability. Education and supportive self-management approaches could reduce the burden of headache disability. We tested the effectiveness of a group educational and supportive self-management program for people living with chronic headaches.